Aquellos hermanos nuestros… Ciudadanía y exclusión en los territorios conquistados - Pani, Erika (El Colegio de México, A.C., 2021)
This text explores the status of the inhabitants of the territories that came under US jurisdiction after the triumph of the United States in its war against Mexico (1846-1848). Through cases that reached the Supreme Courts of New Mexico, California an other states, the essay analyzes the establishment of mechanisms for the integration of Mexicans within the US political community through legislation and jurisdiction.